Assessment of Depression and Anxiety Among Admitted People With Heart Disease Conditions: A Cross-Sectional Hospital-Based Study in a Bangladeshi Population During the COVID-19 - Amin, Mohammad Ashraful; Ahmed, Mohsin; Nahin, Sabrina; Kakoly, Nadira Sultana (Frontiers in Psychiatry, 2022)
Objective Depression and anxiety are widespread and chronic among patients with heart disease. We wanted to determine the proportion of heart patients with depression and anxiety levels as well as factors contributing toward depression and anxiety among hospitalized heart disease patients in Dhaka, Bangladesh during the COVID-19 era. Methods The study comprised a total of 384 participants with a confirmed heart disease diagnosis. We conducted a cross-sectional study from 5th March to 27th June 2021. The hospital-based study admitted patients sequentially with a new or pre-existing heart disease diagnosis to one of Dhaka's two leading hospitals. The Hospital Anxiety and Depression Scale screened all individuals for depression and anxiety. Result Most of the respondents (88.2%) were male and within the age categories of 51–60 years (32.81%). 96.6% of the patients were married, 30% had no income, 36.6% had only completed classes 1–5, and 47% resided in rural areas. Approximately 36% of the study participants were former smokers, with 31% current smokers. Borderline abnormal and abnormal levels of anxiety and borderline abnormal and abnormal levels of depression were found in (23.9%, 49.4%) and (55.7%, 13.3%), respectively, of hospitalized patients. Age, residence, profession, monthly income, and chronic disease were significant predictors of anxiety, while only gender remained significantly associated with depression. Conclusion Hospitalized Bangladeshi patients with heart disease had moderate levels of depression and anxiety. There is a need to develop a quick screening approach in hospitals dealing with hospitalized patients with heart disease to identify those needing extra evaluation and care.